The Role of Lexical-Semantic Neighborhood in Object Naming: Implications for Models of Lexical Access - Bormann, Tobias (Frontiers in Psychology, 2011)
The role of lexical-semantic neighborhood is relevant to models of lexical access. Recently it has been claimed that the size of the cohort of activated competitors affects ease of lexical selection in word production as well as the effect of semantically related distractors in picture-word interference tasks. Three experiments are reported in which subjects had to name pictures from large and small semantic categories (cf. “lion”, “hammer” versus “funnel”, “cage”). In Experiment 1, naming impaired subjects exhibited semantic errors for targets from large categories. No semantic but many omission errors occurred for targets from small categories suggesting that few competitors were available for these ‘low competition targets’. In contrast in two experiments with unimpaired subjects, targets were named equally fast. These experiments were sensitive enough to yield a highly significant repetition effect in Experiment 2. Contrary to the explicit predictions of a recent proposal, semantically related distractors caused interference for both groups of words in Experiment 3. The results suggest no role of neighborhood size in the naming of unimpaired individuals. Implications for models of lexical selection are discussed.